Lubricants, industrial oils and related products (Class L). Family D (compressors). Specifications of categories DRA, DRB, DRC, DRD, DRE, DRF and DRG (lubricants for refrigerating compressors) Part 3, (9th October 2019) - British Standards Institution,
No abstract available